Mengkonstruksi Identitas Diapora Maluku di Negeri Belanda - Nur Aisyah Kotarumalos (Masyarakat Indonesia, 2010)
The Moluccans were one of the ethnic minorities transported to the Netherlands after the Second World War. They were the ex-KNIL soldiers (Dutch colonial army) who intended to demobilise to Ambon at the end of their contract. However the political situation was not conducive as the RMS (Republic of South Moluccas) was proclaimed in Ambon. Finally, the Dutch government saw no other option except to bring these soldiers together with their families to the Netherlands.This article investigates aspects of the practice of Moluccan identity in a diasporic context in which people identify, participate, negotiate and construct their identity in the Netherlands. I begin by addressing the historical and the contemporary components of being a Moluccan in the Netherlands, and argue that the history of transportation to the Netherlands itself constitutes an empowering narrative of survival and a key element in the formation of an ethnic identity among Dutch society.Keywords: Maluku, KNIL, the Netherlands, diaspora, and identity